Inovasi Pendidikan Karakter "BeST" (Bersihkan Sampah Tanpa Diperintah) di Sekolah Dasar Negeri Siwarak Wetan - Rohmat, Rohmat; Fajar, Wildan Nurul (Indo-MathEdu Intellectuals Journal, 2026)
The culture of cleanliness in schools is still dominated by adherence to teacher instructions, so students' independent initiatives in maintaining cleanliness have not developed optimally. This condition indicates the need for character education innovations that can shape positive habits sustainably. This study aims to describe the implementation of the BeST (Clean Up Trash Without Being Ordered) character education innovation in developing students' independent initiatives at Siwarak Wetan Public Elementary School. The study used a descriptive qualitative approach with 124 students in grades I-VI as subjects. Data were collected through observation, interviews, teacher diaries, reflection sheets, and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The implementation of BeST was carried out through the BeST Face Board, Initiative Coins, and 2-Minute Reflections. The results showed that the number of independent clean-up actions increased by 150%, from 34 actions in the 3rd week to 85 actions in the 8th week. In addition, 87.5% of students showed initiative to clean up trash without being ordered and the amount of scattered trash during recess decreased by around 60–70%. These findings indicate that the BeST innovation is effective in building positive habits in students and has the potential to be implemented as a positive reinforcement-based character education model in elementary schools